(3x+5)+(2x-9)-(4x+3)
Answers
Answered by
0
Final Result :
x - 7
Processing ends successfullyAnswer:
=x−7
Explanation:
(3x+5)+(2x−9)−(4x+3)
[Multiplying the sign with the brackets]
=3x+5+2x−9−4x−3
=3x+2x−4x+5−9−3
=x−7
~Hope this helps!
x - 7
Processing ends successfullyAnswer:
=x−7
Explanation:
(3x+5)+(2x−9)−(4x+3)
[Multiplying the sign with the brackets]
=3x+5+2x−9−4x−3
=3x+2x−4x+5−9−3
=x−7
~Hope this helps!
Similar questions
Physics,
9 months ago
India Languages,
9 months ago
Biology,
9 months ago
Math,
1 year ago
Math,
1 year ago
India Languages,
1 year ago
Hindi,
1 year ago